Quality of life in Malaysian colorectal cancer patients. (17th April 2013) - Wan Puteh, Sharifa Ezat; Saad, Natrah Mohd.; Aljunid, Syed Mohd; Abdul Manaf, Mohd Rizal; Sulong, Saperi; Sagap, Ismail; Ismail, Fuad; Muhammad Annuar, Muhd Azrif
Abstract: Introduction: The rapidly increasing of incidence colorectal cancer (CRC) in Malaysia and the introduction of new treatments that prolong survival advocating treatment outcome measures such as patients' quality of life (QOL) are evaluated in this study. The study aims to determine QOL in CRC patients according to cancer stage and age. Methods: A cross‐sectional study was performed from June to December 2011 at four public tertiary hospitals. The European Organization for Research and Treatment in Cancer (EORTC) Quality of Life Questionnaire Core‐30 (EORTC QLQ C‐30) questionnaire was used through face‐to‐face interview and the medical records of 160 respondents were reviewed. Results: The mean age of respondents was 58.47 ± 12.04 years with 57.5% of respondents being male and 42.5% female. The majority of respondents were in CRC stages III and IV. Median global health status (GHS) score was 83.33 (IQR 16.67). Sikhs and Indians had a higher median GHS score compared to other ethnicities (Kruskal–Wallis, χ 2  = 12.12, p = 0.007). Emotional, cognitive and social functions were higher in respondents with earlier stage of disease (Kruskal‐Wallis, χ2 = 6.06, 6.36, 10.58, p = 0.048, 0.042, 0.005). Median pain, dyspnea, diarrhea and financial implication scores were significantly higher in advanced stage of disease (Kruskal‐Wallis, χ 2  = 9.31, 6.26, 6.77, 7.28, p = 0.010, 0.044, 0.034, 0.026). Median diarrhea score (p = 0.012) was significantly different between age groups. Discussion: Emotional, cognitive and social functions deteriorate with advanced stage of disease. Patients with advanced stage disease experience more pain, dyspnea, diarrhea and financial implications. A systematic screening program to detect cases as early as possible is essential nationwide.